The influence of progesterone and prostaglandin F2α on decorin and the adhesion of caruncular epithelial cells of bovine placenta at early‐mid pregnancy—Part II. Issue 7 (19th May 2021) - Jamioł, Monika; Wawrzykowski, Jacek; Kankofer, Marta
Abstract: One of the most important processes determining the proper course of gestation and its physiological termination in cows is the adhesion of epithelial cells allowing for direct contact of maternal and foetal parts of the placenta. Throughout pregnancy, placental cells are under strict hormonal control, which among others regulates the concentration and activity of specific proteins participating in the extracellular matrix remodelling of foetal membranes. The aim of the study was to evaluate the influence of progesterone and prostaglandin F2α on the adhesion of epithelial cells at early‐mid pregnancy in cows. Additionally, the impact of selected hormones on anti‐adhesive properties of decorin was evaluated. Caruncular epithelial cells were isolated from healthy cows during pregnancy, immediately after slaughter. Primary cell cultures derived from the 2nd and 4th month of gestation were used in the experiments. The viability of cells was assessed by MTT assay. The adhesion of cells to fibronectin was measured spectrophotometrically. The activity of metalloproteinases was confirmed by the metalloproteinase assay. Progesterone (10 –5 and 10 –7  mol/L) and prostaglandin F2α (10 –4, 10 –5 and 10 –7  mol/L) increased the viability of bovine caruncular epithelial cells in the 2nd month of pregnancy. The treatment with prostaglandin F2α significantly reduced the number of adherent cells from the 2nd month of gestation at the doses of 10 –4 and 10 –5  mol/L. Both progesterone and prostaglandin F2α were shown to have an effect of decorin resulting in both a decrease in metalloproteinase activity and an increase in adhesion of cells to fibronectin.